2013
DOI: 10.1186/1471-244x-13-290
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional rehabilitation in anorexia nervosa: review of the literature and implications for treatment

Abstract: Restoration of weight and nutritional status are key elements in the treatment of anorexia nervosa (AN). This review aims to describe issues related to the caloric requirements needed to gain and maintain weight for short and long-term recovery for AN inpatients and outpatients.We reviewed the literature in PubMed pertaining to nutritional restoration in AN between 1960–2012. Based on this search, several themes emerged: 1. AN eating behavior; 2. Weight restoration in AN; 3. Role of exercise and metabolism in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
3
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 84 publications
2
105
3
11
Order By: Relevance
“…Providing such big amounts of food to the inpatient could cause an increase in the level of anxiety and, consequently, treatment resistance (11). Furthermore, abdominal discomfort and psychological distress may appear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Providing such big amounts of food to the inpatient could cause an increase in the level of anxiety and, consequently, treatment resistance (11). Furthermore, abdominal discomfort and psychological distress may appear.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is caused by a shift in fluid and electrolytes (particularly phosphate) from the extracellular to intracellular spaces upon refeeding, when insulin is released in response to an influx of nutrients (particularly carbohydrate). This results in electrolyte abnormalities, in particular hypophosphatemia, hypokalemia, and hypomagnesemia, glucose intolerance and thiamine deficiency, and can cause muscle weakness, delirium, coma, ataxia, arrhythmias and congestive heart failure or arrest (11). A review of the literature has revealed an average incidence rate of refeeding hypophosphatemia of 14% (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Food variety is important when establishing meal plans as well as foods that are higher in energy density. However, Marzola, E. et al (2013), reported that people must consume adequate calories, starting slowly, and increasing at a measured pace.…”
Section: Methodsmentioning
confidence: 99%